2019
DOI: 10.1111/febs.14789
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine metabolism: identification of a key residue in the acquisition of prephenate aminotransferase activity by 1β aspartate aminotransferase

Abstract: Alternative routes for the post‐chorismate branch of the biosynthetic pathway leading to tyrosine exist, the 4‐hydroxyphenylpyruvate or the arogenate route. The arogenate route involves the transamination of prephenate into arogenate. In a previous study, we found that, depending on the microorganisms possessing the arogenate route, three different aminotransferases evolved to perform prephenate transamination, that is, 1β aspartate aminotransferase (1β AAT), N‐succinyl‐l,l‐diaminopimelate aminotransferase, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Mutating these two residues converted Arabidopsis PPA-AT to a general aromatic amino acid aminotransferase having broad substrate specificity (137). X-ray crystal structure analyses of plant and bacterial PPA-ATs further revealed the molecular basis of prephenate substrate recognition and identified two additional residues that further enhance prephenate specificity (140,201). Thus, these residues likely played key roles in the evolution of PPA-ATs that allow plants to synthesize Phe and tyrosine via the arogenate pathway.…”
Section: Molecular Basis Of the Evolution Of Plant Prephenate Aminotrmentioning
confidence: 97%
See 2 more Smart Citations
“…Mutating these two residues converted Arabidopsis PPA-AT to a general aromatic amino acid aminotransferase having broad substrate specificity (137). X-ray crystal structure analyses of plant and bacterial PPA-ATs further revealed the molecular basis of prephenate substrate recognition and identified two additional residues that further enhance prephenate specificity (140,201). Thus, these residues likely played key roles in the evolution of PPA-ATs that allow plants to synthesize Phe and tyrosine via the arogenate pathway.…”
Section: Molecular Basis Of the Evolution Of Plant Prephenate Aminotrmentioning
confidence: 97%
“…in actinobacteria); and branched-chain aminotransferase (e.g. in cyanobacteria) (135,137,140). Notably, plant PPA-ATs are most closely related to the Ib aspartate aminotransferase-type of Chlorobi/Bacteroidetes (135,137).…”
Section: Alternative Phenylalanine Biosynthetic Pathways For Phenolicmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolutionary analyses of the PPA-AT and ADT enzymes suggested that an ancestor of green algae and land plants appear to have acquired both of these two enzymes from an ancestor of Chlorobi/Bacteroidetes bacteria, likely through horizontal gene transfer (Dornfeld et al, 2014). Some cyanobacteria also have PPA-AT enzymes but with a distinct evolutionary origin from those of plants and Chlorobi/Bacteroidetes bacteria (Graindorge et al, 2014; Giustini et al, 2019). Thus, these dual primary metabolic pathways of isoprenoid and phenylalanine biosynthesis appear to have evolved in a common ancestor of Plantae.…”
Section: Ancient Diversification Of Ipp and Phenylalanine Biosynthetimentioning
confidence: 99%
“…At the protein level (Figure 2b), the RTY1-1 point mutation translates into a P213S amino acid exchange [29], which is likely to cause major structural changes in the RTY enzyme. Protein modelling of RTY and RTY1-1 against the 1.7 Å crystal structure of a closely related prephenate aminotransferase from Arabidopsis [30] (PDB: 6F5V) and subsequent structure predictions suggested the loss of one -helix motif in RTY1-1 (13 -helices) relative to the wild-type protein (14 -helices) in the C-terminal part of the protein. Against our initial expectations, the ami1/rty double mutants still showed an auxin overproduction-related phenotype (Supplementary Figure S1), suggestive of a remaining conversion of IAM to IAA.…”
Section: The Introgression Of the Ami1-2 Mutation Into Rty1-1 Is Not mentioning
confidence: 99%